2022
DOI: 10.1111/jbi.14499
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation drives species accumulation whereas temperature drives species decline in Himalayan vertebrates

Abstract: Aim Many studies have explored taxon‐specific richness patterns with elevation, but few have concurrently evaluated different mechanisms to explain elevational patterns across multiple taxa. We used a novel, cross‐taxa approach to study species richness patterns combined with a framework that tests drivers of species accumulation versus decline along the elevational gradient in the Himalayas. Location The Himalayas. Taxon Mammals, birds and amphibians. Methods We used geographical and elevational data of 314 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
0
1
Order By: Relevance
“…This pattern of declining diversity with increasing elevation contrasts with results from many other studies that found a mid‐domain (middle‐elevation peak) effect (Herzog et al., 2005 ; Hu et al., 2022 ; McCain, 2005 ). Small mammal surveys conducted on different parts of Mt Kenya (Musila et al., 2019 ; Onditi et al., 2022 ) showed that the pattern may vary depending on which side of the mountain was surveyed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This pattern of declining diversity with increasing elevation contrasts with results from many other studies that found a mid‐domain (middle‐elevation peak) effect (Herzog et al., 2005 ; Hu et al., 2022 ; McCain, 2005 ). Small mammal surveys conducted on different parts of Mt Kenya (Musila et al., 2019 ; Onditi et al., 2022 ) showed that the pattern may vary depending on which side of the mountain was surveyed.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, it is possible that large mammal diversity does show a mid-domain effect, but that it is spread over a larger elevational gradient. Indeed, the Mt Kilimanjaro study, which focused on elevational ranges from 750 to 4500 m, did find a mid-domain effect but that the peak diversity was around 2100 m, roughly 200 m lower in elevation than our lowest camera trap (Gebert et al, 2019), a pattern that was similarly observed in a similar elevation study in the Himalayas (Hu et al, 2022).…”
Section: Habitat Mid-elevation Trends and Species Specializationsupporting
confidence: 77%